The Diversity Species of Medicinal Plants in The Martelu Purba Nature Reserve, North Sumatra - Jelly Permana Purba; Ahmad Baiquni Rangkuti; Arida Susilowati; Onrizal; Rambey, Ridahati (Journal of Sylva Indonesiana, 2022)
Indonesia was known as a country that has high biodiversity, some of them are various types of medicinal plants. Since the first, Indonesian people have used medicinal plants in traditional medicine. This research was conducted in the Martelu Purba Nature Reserve (MPNR), Purba District, Simalungun Regency, North Sumatra. MPNR is a nature reserve consisting of high biodiversity, some of them are medicinal plants. However, the information on medicinal plants in this area is rarely documented even though they have a meaningful contribution as traditional medical treatments for indigenous communities. This study aims to identify all plant species found in the MPNR. This method of research was carried out by exploring key informants, namely the manager of the nature reserve and the local community. Determination of the number of respondents is done by the snowball sampling method. The results showed that there were 44 species of medicinal plants found in the MPNR consisting of 33 families, where the most families were from the Arecaceae family, which was 17.24%. Based on habitus, medicinal plants found inÂ  MPNR consist of 20 tree species (45.45%), 13 herb species (29.54%), 5 palm species (11.36%), 4 shrub species (9.09 %), and 2 species from epiphytes (4,54%). Based on the intended use of medicinal plants used as fever, cough, diarrhea, diabetes, wounds, asthma, malaria, and others. Based on the part of the plant that has been used, 19 species from leaves (42.22%), 7 species from fruit/seed (15.90%), 6 species from all plant parts (13.63%), 5 species from bark (11.36%), 2 species from roots (4.54%), 1 species from resin (9.09%), 1 species from the flower (9.09%), 1 species from bark and seeds (9.09%), 1 species from wood (9 .09%), and 1 species from bark and leaves (9.09%). Medicinal plant species found in the MPNR must be conserved to maintain their sustainability and can be used sustainably.